Memory of Conflicts and Perceived Threat as Relevant Mediators of Interreligious Conflicts - Setiawan, Tery (Religions, 2022)
The present study investigated to what extent memory of conflict and perceived threat explain the relation between religiosity and supporting interreligious conflicts between Muslims and Christians in Indonesia. We employed data from the survey of the interreligious conflicts in 2017, involving 2026 adults from five hotspot regions: Aceh Singkil, South Lampung, Bekasi, Poso, and Kupang. Our confirmatory factor analysis and measurement invariance demonstrated that all employed scales were valid and reliable across religious groups. Our structural equation modelling showed that while the memory of conflicts was only positively related to supporting lawful protests, the perceived threat was shown to be strongly related to supporting both lawful and violent protests. This shows that memory of past physical injuries is not highly susceptible to exclusive behaviours against the religious outgroup. However, it is the individuals’ evaluation of the religious outgroup as a result of past conflicts which encourages exclusionary behaviours against them. These findings provide empirical insights into the importance of the aftermath of interreligious conflicts and how they can be used to avoid future clashes.